Risk Factors for Clonorchis sinensis Infection in Residents of Binyang, Guangxi: A Cross-Sectional and Logistic Analysis Study - Xu, Meng; Jiang, Yanyan; Yin, Jianhai; Cao, Shengkui; Shen, Yujuan; Cao, Jianping (Frontiers in Public Health, 2021)
Background: Clonorchiasis is a serious food-borne parasitic disease caused by Clonorchis sinensis infection. C. sinensis, a major fish-borne trematode, is a known causative agent of cholangiocarcinoma. The risk factors of C. sinensis infection include individual eating behaviors and environmental factors. Here, we evaluate the C. sinensis infection rate and the associated risk factors among residents in Binyang County, Guangxi, China. Methods: In 2016 and 2017, five villages from Binyang, Guangxi were selected by multistage cluster random sampling for a cross-sectional study. A triplicate modified Kato-Katz thick smear method was used to examine C. sinensis eggs in fecal samples. Both bivariate and multivariate logistic regression analyses were carried out to identify the risk factors for C. sinensis infection. Results: A total of 1977 fecal samples were collected from residents and examined. The overall prevalence of C. sinensis infection in Binyang County was 20.49% (405/1977). The mean age of participants was 39.42 ± 23.48, and the highest infection rate was seen in those aged 40-49 (33.72%), followed by those aged 50-59 (31.83%). Bivariate logistic regression analysis showed significant intra-class differences in infection rate between genders, ethnic groups, age groups, occupations, educational levels, raw fish consumption habits and whether or not they were in contact with cats and dogs. Multivariable logistic regression analysis showed that higher infection rates were significantly associated with males, Zhuang, age, eating raw fish frequently and those in contact with cats and dogs. Occupation and education level are considered confounding factors (P > 0.05). Conclusions: High levels of C. sinensis infection were recorded among residents in Binyang County, Guangxi. This study provides relevant baseline data for improving the prevention and control measures against clonorchiasis in Bingyang. In addition, the important impact of cats and dogs contact on the transmission of C. sinensis should be considered in this region.